Concepções de professoras: Um estudo sobre a contribuição da didática na perspectiva histórico-cultural - Alves, Raiane Santos (2024)
This research is part of the Knowledge and Educational Practices research line within the Graduate Program in Education at the Federal University of Uberlândia. Its main objective is to analyze the contributions of didactics to the initial teacher training process, based on the perspective of Cultural-Historical Psychology. The study involved four Basic Education teachers working in Elementary Education I at municipal schools in a town in the interior of Minas Gerais, Brazil. Adopting a qualitative approach, the field research was conducted through semi-structured interviews, which served to collect data on the teachers' experiences and conceptions of didactics. The interviews explored themes related to initial training, learning theories, didactic practices, and the organization of teaching work. Data were transcribed and analyzed qualitatively, with Cultural-Historical Psychology serving as the central theoretical framework. The data analysis was organized around three main axes: the choice of profession and teacher training; the contribution of didactics to the development of pedagogical skills; and the internalization and development of pedagogical competencies in daily practice. The interviews revealed that teachers aim to develop pedagogical strategies tailored to the needs of their students, promoting inclusive and transformative education. However, they also face institutional and structural challenges that hinder the implementation of practices aligned with their training and theoretical-methodological foundations. The results indicate that didactics plays a crucial role in the development of reflective and contextualized educational practices, emphasizing the importance of continuous and adaptive training to address classroom challenges and promote equitable and high-quality education. Thus, didactics, understood as the science of teaching, provides essential theoretical and practical tools for a pedagogical approach that fosters continuous reflection and adaptation to students' needs, contributing to broader research efforts in the field of education.